The connection between the smart city concept and human resource management, with a special focus on the role of competences and corporate competitiveness - Greutter-Gregus, Éva; Greutter, Zoltán Gergely (Studia Mundi – Economica, 2024)
The trend today is that more and more cities are becoming smart. This process can be strengthened if a municipality has a high proportion of well-educated workers with the right competences who can contribute to the excellence of a company by increasing the competitiveness of the organisation and the city. In addition, other economic, environmental and social factors, such as increasing GDP and employment rates, reducing environmental impacts, etc., are necessary to become a smart city. The literature review has clarified the key concepts and highlighted the importance of the topic. Our research has analysed the capital cities of the Visegrad Group in 6 dimensions, using a total of 19 indicators, and has determined their index values per dimension and complexity. The focus of our research was on the people dimension. The aim of this research is to explore the index scores per dimension and the complex index scores of the cities under study. Bratislava scored the highest in this dimension, with Prague coming second. Warsaw came third and Budapest last in the comparison. In terms of the complex index, Bratislava is the smartest of the cities surveyed.